Urban carbon footprints across scale: Important considerations for choosing system boundaries. (1st February 2020) - Chen, Shaoqing; Long, Huihui; Chen, Bin; Feng, Kuishuang; Hubacek, Klaus
Highlights: We develop a framework to consistently interpret carbon footprints of cities. Main destinations of outsourced carbon emissions from megacities are similar. Key infrastructure contributes >70% of carbon emission in urban imports. Different carbon footprints show divergent sensitivities to mitigation policies. Abstract: Cities dominate global anthropogenic carbon emissions. Here, we develop an approach to interpret carbon footprints of cities by focusing on their system boundaries, double counting recognition, spatial paths and policy sensitivities. Using four megacities in China as a case study, we quantify and map urban carbon footprints from various accounting perspectives: territorial carbon emissions, community-wide infrastructure carbon footprint, consumption-based carbon footprint, wider production carbon footprint, and full-scope carbon footprint. We find that the megacities' infrastructure carbon footprints are dominated by electricity-related emissions, whereas their consumption-based carbon footprints are significantly impacted by imports of both electricity and other products and services. Over 55% of the full-scope carbon footprints (sums of all three scopes) of Beijing and Shanghai can be attributed to upstream emissions, while in Chongqing and Tianjin territorial emissions are more important. Key urban infrastructure contributes over 70% to the total carbon emissions in import supply chains, determining the spatial paths and the carbon intensities of imports for these megacities. The main destinations of outsourced carbon emissions across the country from the megacities are found to be similar due to market domination of bulk suppliers of infrastructure-related and other carbon-intensive products. In addition, double counting of certain footprint indicators is considered small in this case, but could be amplified with increasing number of cities being assessed.